Short-Run and Long-Run Effects of Non-Oil Trade Export on Economic Growth in Nigeria: Array - Ogunsanwo, Odunayo Femi; Obisesan, Oluwaseun Grace; Olowo, Samson Oluwole (Acta Universitatis Danubius. Œconomica, 2020)
This study examined the short and long run effects of non-oil trade export on economic growth in Nigeria. Descriptive statistics and inferential statistics (unit root test, Johansen cointegration and error correction mechanism) were employed as the estimation techniques. The time series data on non-oil export (proxied by non-oil total trade, balance of trade, exchange rate and inflation rate); and economic growth (proxied by growth rate of Real Gross Domestic Product) were sourced and obtained from the Central Bank of Nigeria Statistical Bulletin and Nigerian Bureau of Statistics over a period of thirty (33) years (1986–2018). The study showed that non-oil total trade, balance of trade and exchange rate have positive and significant effects on economic growth in Nigeria while inflation rate has no significant effect on economic growth in Nigeria. Based on the finding of the study, it was concluded that non-oil trade export has positive and significant effects in the short run and long run on economic growth in Nigeria. It is recommended that full attention should be directed to the non-oil sector in other to make our produce competitive in international market.